Analysis and Characterization of the Immunogenicity of Rhoptry Protein 18 - Masoud Foroutan; Amir Karimipour-Saryazdi; Ali Dalir Ghaffari; Hamidreza Majidiani; Arezo Arzani Birgani; Elaheh Karimzadeh-Soureshjani; Shahrzad Soltani; Hany M Elsheikha (Bioinformatics and Biology Insights)
Rhoptry protein 18 (ROP18) is a key virulence factor secreted into host cells during the invasion of Toxoplasma gondii ( T. gondii ) and plays an important role in the pathogenesis of infection. Due to its potential as a vaccine candidate, this study aimed to characterize several properties of the T. gondii ROP18 (TgROP18) protein to support its inclusion in vaccine formulations. Using a range of bioinformatics tools, we investigated its T-cell and B-cell epitopes, physicochemical properties, subcellular localization, transmembrane domains, and tertiary and secondary structures. Our analysis revealed 48 post-translational modification sites in TgROP18. The secondary structure was composed of 4.87% beta-turns, 38.45% random coils, 42.42% alpha helices, and 14.26% extended strands. Several potential T- and B-cell epitopes were identified on ROP18. The Ramachandran plot of both crude and refined models showed that 85.8% and 95.3% of the amino acid residues, respectively, fell within favored regions, indicating energetically stable conformations. Allergenicity and antigenicity assessments indicated that TgROP18 is a nonallergenic, immunogenic protein. Predictions using the C-ImmSim server suggest that TgROP18 can stimulate humoral and cell-mediated immune responses, based on antibody titers and cytokine profiles following antigen administration. These findings provide baseline data for future investigations focused on the potential of TgROP18 in developing therapeutic strategies against toxoplasmosis.